(untitled) (Hong Kong Journal of Ophthalmology, 2022)
We report a case of chronic dacryocystitis treated with dacryocystosclerotherapy with doxycycline injection in an 89-year-old woman. At the 12-month follow-up, the dacryocystitis was resolved, and there was a residual sac cavity with a trace amount of mucoid discharge without requiring further treatment.